CREATIVELY EXPLORING EARLY SCIENCE TEACHING AND LEARNING IN PRESCHOOL - Ros Nor Mala; Dr Madhya Zhagan (Journal of Islamic, Social, Economics and Development, 2024)
Teacher exploration and creativity are two important elements in the early science teaching and learning process in preschool. This study aims to explore early science teaching and learning creatively in preschool. Aspects of the study related to the extent in which teachers implement early science teaching and learning creatively in preschool. The research design is qualitative through a case study of various places on six expert preschool teachers as participants in the study involving two districts. Interview techniques, observation and document content analysis were used over a period of six months. The validity and reliability of instruments and study data are obtained through peer review, member check, audit trail, triangulation, preliminary study, researcher as instrument and study period. Thematic data analysis using the support of Nvivo version 12 software. The findings of the study found six themes that exist which are exploratory activities, activities should be interesting and fun, concrete use of materials and child-centered activities, implemented in and outside the classroom, modification of activities and learning space and need planning and preparation,. Nevertheless, teacher creativity depends and is closely related to the knowledge, experience and belief of teachers towards the process and activities of early science teaching and learning in preschool. In summary, early science teaching and learning through creative exploration is important to be highlighted so that it is more meaningful and can attract children's interest in science to build and shape the future of national development in accordance with development practices that are appropriate for children.